Pengaruh Penerapan Green Accounting, Kinerja Lingkungan dan Corporate Social Responsibility (CSR) Terhadap Profitabilitas Perusahaan Sektor Basic Materials - Ica Intan Piwari; Citra Indah Merina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of Green Accounting, Environmental Performance, and Corporate Social Responsibility (CSR) on the profitability of Basic Materials sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2023. This research employs a quantitative approach using purposive sampling and obtains 18 companies as samples over two years of observation, resulting in 36 data points. The independent variables in this study are Green Accounting, Environmental Performance, and CSR, while the dependent variable is profitability, measured by the Return on Assets (ROA) ratio. The data analysis technique used is multiple linear regression with the aid of SPSS version 27. The results show that environmental performance and Environmental Corporate Social Responsibility (CSR) have a positive effect on profitability, whereas Green Accounting does not have a significant effect. This research contributes to the development of stakeholder theory and corporate sustainability disclosure practices in improving financial performance.